Diagnostic accuracy of cerebroplacental ratio in anticipating adverse perinatal outcome in uncomplicated appropriate for gestational age pregnancies at term - Abhijan Maity; Bhawana Sonawane; Anagha Deshpande; Sunita Bhutada (Wolters Kluwer -Medknow Publications, 2024)
Introduction: Anticipating which babies are in danger of experiencing poor outcomes during the perinatal period in uncomplicated appropriate for gestational age (AGA) pregnancies at term is difficult in obstetric practice. Cerebroplacental ratio (CPR) is emerging as a significant indicator of negative perinatal results. The current study sought to establish how effective CPR is in predicting negative perinatal outcomes in term uncomplicated AGA pregnancies. Materials and Methods: This study was a hospital-based prospective observational cohort study conducted at a single center. Patients were chosen depending on different criteria for inclusion and exclusion. A prenatal ultrasound with a color Doppler scan was carried out to calculate CPR. Patients were grouped according to their last CPR measurement before delivery into either normal CPR or pathological CPR categories. Doppler results did not impact clinical decisions and delivery followed institutional protocols. After childbirth, data on the outcome of the perinatal period were obtained from the patients' medical records. Negative perinatal outcomes were assessed through the delivery method, APGAR score, perinatal morbidity, and perinatal mortality. These outcomes were correlated with CPR. Results: The research included 605 women, separated into normal and pathological CPR groups. Of these, 153 (25.3%) were classified in the pathological CPR category, whereas 452 (74.7%) exhibited normal CPR. In our study, there were 138 patients who experienced adverse perinatal outcomes in the pathological CPR group, whereas 44 patients had such outcomes in the normal CPR group. The diagnostic accuracy of pathological CPR to predict any negative perinatal result was 90.25%. Conclusions: CPR shows potential in detecting fetuses at risk in full-term uncomplicated AGA pregnancies.